2013
DOI: 10.1111/aor.12024
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Single‐Lumen Cannula Venovenous Extracorporeal Membrane Oxygenation: A French Center Experience

Abstract: Single-lumen cannula venovenous (VV) extracorporeal membrane oxygenation (ECMO) is a special extracorporeal life support (ECLS) technique used for neonatal and pediatric refractory hypoxemia. This is an alternative flow rate ECLS that consists of successive clamping on the drainage and the injection lines. Currently, the Armand-Trousseau's pediatric intensive care unit remains the only pediatric ECMO center proposing this partial assistance. This article details a technical note and a retrospective analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…Drainage and return by the same cannula is permitted by means of a non-occlusive pump and successive clamping on the drainage and injection lines [31]. The flow rates used are a little higher (about 30% of the cardiac output).…”
Section: Questionsmentioning
confidence: 99%
“…Drainage and return by the same cannula is permitted by means of a non-occlusive pump and successive clamping on the drainage and injection lines [31]. The flow rates used are a little higher (about 30% of the cardiac output).…”
Section: Questionsmentioning
confidence: 99%
“…L'alternance drainage et réinjection par la même canule est permise grâce à l'utilisation d'une pompe non occlusive et d'un clamp alternatif [31]. Les débits utilisés sont un peu plus éle-vés (environ 30 % du débit cardiaque).…”
Section: Particularités Pédiatriquesunclassified
“…In our ECMO experience, the ischemic brain lesions occurred in 20% of newborns [20]. Rollins et al reported up to 62% of cases that had abnormal MRIs after neonatal ECMO, whereas ultrasound imaging was abnormal in only 24% of the cases [21].…”
Section: Discussionmentioning
confidence: 99%